Perbandingan Efikasi Vaksin Produk Intra- dan Ekstraseluler Aeromonas Hydrophila untuk Menanggulangi Penyakit Motile Aeromonas Septicemia (Mas) pada Lele Dumbo (Clarias sp.) - Dini Siswani Mulia; Cahyono Purbomartono (Universitas Gadjah Mada, 2007)
The aims of this research were to evaluate the eficacy of intra- and extracellular products vaccines of Aeromonas hydrophila to control Motile Aeromonas Septicemia (MAS) in catfish (Clarias sp.). Catfish with 10-13 cm of total length were used for the experiment with three treatments in five replicates. The treatments were vaccinations with (1) A: intracellular product of A. hydrophila; (2) B: extracellular product of A. hydrophila; (3) without vaccination (control). Vaccination was conducted by intramuscular injection of 5 µg protein/fish (each fish was injected with 0.1 ml of vaccine). Booster was conducted one week after vaccination. The challenge test was conducted two weeks after booster. The results showed that the survival rate, Relative Percent Survival (RPS), and antibody titer of A treatment was significantly different (PA. hydrophila (A treatment) reached 85.33 and 82.26%, respectively. The highest antibody titer was 1843.2 which was obtained by the A treatment. The results suggested that intracellular product vaccine of A. hydrophila was more effective than extracellular product vaccine.